The importance of indocyanine green near‐infrared fluorescence angiography in perfusion assessment in vascularized omentum lymphatic transplant. Issue 1 (19th June 2018) - Coriddi, Michelle; Kenworthy, Elizabeth; Weinstein, Andrew; Mehrara, Babak J.; Dayan, Joseph H.
Abstract : Background and Objective: Vascularized omentum lymphatic transplant (VOLT) for treatment of lymphedema has become popular because of no risk of iatrogenic lymphedema and abundant lymphatic tissue. However, perfusion to the omentum can be difficult to assess clinically. The purpose of this study was to clarify the incidence and degree of ischemia in the omentum. Methods: A retrospective study was conducted to review indocyanine green perfusion findings on patients undergoing VOLT. Patients were placed into 4 categories based on the percentage surface area of omentum that was ischemic: normal, less than 25%, between 25% and 50%, and greater than 50% ischemic. Spearman correlation was performed to determine whether an association exists between prior abdominal surgery and the presence of ischemia. Results: Twenty‐six patients underwent VOLT for treatment of extremity lymphedema. Twelve (46.2%) patients had normal perfusion, 8 patients (30.8%) had less than 25% ischemia, and 6 patients (23.1%) had 25% to 50% ischemia. Prior abdominal surgery was not significantly associated with the presence of ischemia. Conclusions: Normal flap perfusion is a requisite for successful VOLT harvest. However, over half the patients had some degree of abnormal perfusion irrespective of prior abdominal surgery. Indocyanine green angiography is an important tool in ensuring a healthy lymphatic reconstruction.